If x=2, y= -5, and z= -1, then what does (x-y) (x+y-z) equal?

1 Answer
Apr 19, 2018

Answer:

#(x-y)(x+y-z) = (2+5)xx(2-5+1) = 7xx (-2) = -14#

Explanation:

First, substitute the values of #x#, #y#, and #z#.

#(x-y)(x+y-z) = [2- (-5)][2+ (-5) - (-1)]#

Next, we remove unnecessary addition and subtraction signs to complete the expression.

  • #- and + = -#
  • #- and - = +#
  • #+ and + = +#

So

#(2+5)(2-5+1)#

Next, we complete the expressions inside the brackets (order of operations).

#(7)xx(-2)#

Finally, to complete the expression, we carry out the multiplication:

#-14#